2023
DOI: 10.1186/s12910-023-00888-y
|View full text |Cite
|
Sign up to set email alerts
|

Key ethical issues encountered during COVID-19 research: a thematic analysis of perspectives from South African research ethics committees

Abstract: Background The COVID-19 pandemic presents significant challenges to research ethics committees (RECs) in balancing urgency of review of COVID-19 research with careful consideration of risks and benefits. In the African context, RECs are further challenged by historical mistrust of research and potential impacts on COVID-19 related research participation, as well as the need to facilitate equitable access to effective treatments or vaccines for COVID-19. In South Africa, an absent National Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 52 publications
(48 reference statements)
0
17
0
Order By: Relevance
“…The research hypotheses may not be investigated in time if they are not approved and started at the right time. Also, prioritizing critical issues related to health in the ethics committees should be considered due to the crisis conditions 6 . During the Ebola epidemic, for example, clinical trials proceeded non‐stop.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The research hypotheses may not be investigated in time if they are not approved and started at the right time. Also, prioritizing critical issues related to health in the ethics committees should be considered due to the crisis conditions 6 . During the Ebola epidemic, for example, clinical trials proceeded non‐stop.…”
Section: Resultsmentioning
confidence: 99%
“…• Human ethics in study enrollment 5,11,41 • fear of infection among participants 7,41,50 • High risk participants (Elderly people, pregnant women) 41,45 • Obtaining informed consent form 7,24,49 • Expansion and diversity in communication networks 6,19 • Using online methods to collect information and interview 19,37 • Changing the type of execution 19 • Creating online classes, online exercises, using videos and virtual networks 11,56 • Creating online platforms for responding to participants, and completing questionnaires 49,56 • Considering financial incentive 56 Administrative issues…”
Section: Issues Related To Researchers or Investigatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these contributions focus exclusively on one ERC, usually associated with an academic or health care institution. The literature includes descriptions of ERC operations during the pandemic in Central America and the Dominican Republic [17], China [18], Ecuador [19], Egypt [20], Germany [21], India [2224], Iran [10], Ireland [25], Kenya [26], Kyrgyzstan [27], Latin America [28], the Netherlands [29], Pakistan [30], South Africa [31,32], Turkey [33], and the United States [3436]. Most of these studies reported results from surveys, interviews, focus groups, and documentary analysis, including review of research protocols, ERC meeting minutes, and existing SOPs.…”
Section: Discussionmentioning
confidence: 99%
“…Kyrgyzstan [27], Latin America [28], the Netherlands [29], Pakistan [30], South Africa [31,32], Turkey [33], and the United States [34][35][36] Conversely, several ERCs availed themselves of international guidelines (Box 2), in particular those prepared by WHO [37][38][39][40] and PAHO [41][42][43][44].…”
Section: Discussionmentioning
confidence: 99%